ANALISIS MEKANISME PENERAPAN PPH 22 PADA KANTOR BPKPAD KOTA BANJARMASIN - Nur Winda Amalia; Fatimah; Sustinah Limarjani (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
This study aims to analyze the implementation of the collection, deposit, and reporting of Income Tax (PPh) Article 22 by the BPKPAD of Banjarmasin City. The method used is descriptive with a qualitative and quantitative approach, based on direct observation, documentation, and interviews with the expenditure treasurer of the relevant agency. The results of the study show that although the mechanism for collecting and depositing PPh 22 is in accordance with the provisions of PMK No. 34/PMK.010/2017, there are still delays in reporting through e-Bupot Unifikasi. These findings indicate the need to strengthen internal supervision and improve the technical understanding of tax reporting by officials. This study is expected to serve as an evaluative reference for government agencies in optimizing fiscal compliance